The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology